Assessment of bacterial cellulose membrane produced by Acetobacter xylinum used as scaffold for mouse fibroblast culture - Anh, Nguyễn Thị Kim; Dương, Hoàng Thùy; Hòa, Trần Thị Khánh; Kiều, Nguyễn Thị Thanh (Vietnam Journal of Biotechnology, 2016)
In recent years, bacterial cellulose material has been considered as a potential biotechnological product for biomedical applications. Previous studies described some special properties of bacterial cellulose, such as water holding capacity, high polymerization, high crystallization, high purity, and strength. In this study, bacterial cellulose membrane produced by Acetobacter xylinum was examined for its possibility to use as a scaffold for cell to grow. Firstly, mechanical properties of bacterial cellulose membrane including strength, stress at break, strain at break, and modulus were analyzed. Secondly, cellulose fiber structure was observed with scanning electron microscope. Lastly, biocompatibility of bacterial cellulose membrane was investigated for application as scaffold for cell culture. The results showed that bacterial cellulose membrane had fine fibres arranged to form 3-D porous structured hydrogel. Also, the mechanical qualities of material were suitable for using as a biomaterial. Fibroblast cells isolated from mouse’s skin and tail bone were cultured in Dulbecco's Modified Eagle's Medium supplemented with 10% fetal bovine serum and 1% antibiotics. Cells then collected and sew into bacterial cellulose membrane placed in cell culture disk. At different time points at 1 day, 4 days, and 7 days after sowing the cells, it is clearly seen that cells can adhere, grow and expand on the surface of cellulose membrance placed on cell culture disk, as comparible as cells cultured in disk without cellulose membrance. In conclusion, bacterial cellulose membrane is a suitable material for cell culture as a scaffold. The results observed from this study might be suggestions for next investigations on using bacterial cellulose membrane as scaffold for tissue engineering.